A clinicopathological study on carcinoembryonic antigen in breast cancer - Asagoe, T; Yamoto, H; Hanatani, Y; Horie, F; Nemoto, A; Kidooka, K; Shikata, J (Nihon Gan Chiryo Gakkai shi, 1990)
The production of carcinoembryonic antigen (CEA) by human breast cancer tissue has been studied in relation to the prognosis of 60 patients with breast cancer who were classified in Clinical Stage of UICC I, II and III, and who were treated by radical mastectomy. Tissue CEA was studied in primary tumors using an immunoperoxidase (PAP) method. The obtained results were as followings: 1) Patients who had CEA-negative tumors had significantly higher 10-year survival rates. 2) The positive staining rate of CEA rises as Clinical Stage and metastatic status of lymph nodes advanced. 3) There were significant correlations between staining rate of CEA and classification of histological type and differentiation. 4) There were significant correlations between staining rate of CEA and lymphoid infiltration around main tumor and Sinus Histiocytosis in regional lymph nodes. 5) These results suggest that immunohistological assessment of CEA in breast cancer tissue may provide more precise prognostic information.